FIQH SIYASAH REVIEW OF THE DUALISM OF THE BATAM ENTERPRISE AGENCY AND THE BATAM CITY GOVERNMENT BASED ON GOVERNMENT REGULATION NO. 46/2007 - Afriantita, Selfia; Pulungan, Sahmiar; Lubis, Sofianty (Hukum tata Negara/Siyasah, 2025)
A Fiqh Siyasah Review of the Dualistic System of Government Between the Batam Business Entity (Bp) and the Batam City Government Based on Government Regulation of the Republic of Indonesia Number 46 of 2007 concerning Free Trade and the Free Port of Batam, which discusses regional autonomy implemented in the city of Batam, has resulted in a dualism of authority between the Batam City Government (Pemkot Batam) and the Batam Business Entity (BP Batam). This dualism of authority has resulted in inconsistencies between Pemkot Batam and BP Batam in administering the city of Batam. All efforts by the government have been unable to resolve this issue, so the strategy being pursued is to make Batam a Special Economic Zone. The research method used in this thesis is juridical-normative, which is an approach based on primary legal materials by examining theories, concepts, legal principles, and Law No. 46 of 2007 concerning Free Trade and the Free Port of Batam. The research method used in this thesis is juridical-normative, a juridical-normative approach based on primary legal materials by examining theories, concepts, legal principles, and Law Number 46 of 2007 concerning Free Trade and the Free Port of Batam.Keywords: Dualism of Leadership, Batam Business Entity (BP), Batam City Government